A study on assertiveness level of college students who are doing orienteering sports - Coşkuner, Zeki; Çoban, Bilal; Savucu, Yüksel; Gacar, Atalay; Genç, Eyyup (My University, 2013)
In essence, Assertiveness is an inclination to undertake new and daring enterprises. Namely, it’s the trait of being adventurous. Assertiveness is an important aspect of communication with others, and it’s also a decisive factor of getting engage with people. In this study, it’s aimed to study Assertiveness level of college students who is doing Orienteering Sports in terms of some variables. This study is carried out will a survey of 7 questions regarding students’ personal information and Rathus’ Assertiveness Schedule which contents 30 questions. This study is carried out in Balikesir, Turkey during College Orienteering Sports Olympics. 192 males and 68 females (Total of 260) college students volunteered to participate with the research. Collected data is analyzed with SPSS distribution of frequency, arithmetic sequence and T-Test. Error rate in this study assumed as 0, 5.According to the study, college students who are involved with Orienteering Sports have Assertiveness level of middle, high or highest level as stated by 260 of the participants. Also, it is found that males’ assertiveness level is higher compared to female participants. Besides, students with ages to have higher assertiveness levels. Study also shows that where students come from makes no difference in terms of assertiveness level. As a result, it has been found that students involved in Orienteering Sports have higher assertiveness level and their previous sports history also contributes in a positive way.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Orienteering sports; Assertiveness level; College students